DCAF13 is essential for mouse uterine function and fertility - Qianhui Zhou; Xiaohui Li; Ningjing Wang; Liang Zhang; Enhui Jiang; Kaixuan Wang; Xingyu Yan; Cong Zhang (Cell Death Discovery)
Abstract The incidence of female infertility is a growing worldwide concern and a leading cause of population decline. Therefore, understanding the pathogenesis of infertility is of utmost importance. DDB1 and CUL4 Associated Factor 13 (DCAF13) is a significant component of the CRL4 E3 ubiquitin ligase complex responsible for recognizing substrates and degrading them after polyubiquitylation. DCAF13 has been implicated in oocyte and embryo development, but its role in the uterus remains elusive. To investigate its function, we generated Dcaf13 conditional knockout (cKO) mice and discovered that the uteri of cKO mice became smaller and thinner as they mature, and the embryos were unable to implant, leading to infertility. Mechanistically, we detected aberrant expression of estrogen and progesterone receptors, along with dysregulation of estrogen- and progesterone-responsive genes in the endometrium. This led to insufficient proliferation of endometrial cells in mice. RNAseq analysis revealed an overall increase in transcription of methylation-related genes, including SUV39H2, leading to higher H3K9me3 levels and consequently hindered cell proliferation in the uterus. Furthermore, DCAF13 knockdown resulted in elevated intracellular H3K9me3 levels. In conclusion, these findings suggest that DCAF13 is essential for maintaining the structure of the uterus and fertility. This study potentially contributes to the development of new strategies aimed at improving female reproductive health.